Beyond Weapons of the Weak: Roma Resistance to Securitarian Governance - Ivasiuc, Ana (Romano džaniben, 2023)
Over the last two decades, the Roma in Italy have shifted from being the subject of social policy to being subjected to securitization processes. As a result, the most destitute groups among the Roma in Italy – those living in the so-called campi nomadi – have been increasingly governed through security policies, measures, and apparatuses. Placed in segregated camps, often surrounded by surveillance cameras, and increasingly subjected to police control and repression, the Roma are not passive to the ways in which they are securitized and governed. Grounding my argument in an ethnography of formal and informal policing of the Roma in the peripheries of Rome carried out between 2014 and 2017, I explore how Roma react to their own securitization. I propose a relational approach that goes beyond conceptualizing Romani resistance in terms of the Scottian concepts of `hidden transcripts’ or `weapons of the weak,’ and focus on how Roma attempt to overtly shape their relationships to police, as well as to the material environment in which they are constrained to live.